(untitled) (Journal Of Educational and Psychological Researches, 2018)
Statistics indicate criminal in most countries of the world that the suicide rate continues to increase, as it prevalence manufacturing and complexity of life and the intensification of conflicts and escalating problems of rising suicide rates. And suicide is death intentional, that is, the intentional act that leads to ending the life of the individual and self-on purpose. The current research aims to identify the suicide in terms of its causes and its factors and come up with recommendations for the prevention of suicide. Because suicide is a life-threatening problem has tried several theories of interpretation and stand on its grounds. Considering the theories of psychoanalysis (Freud) that suicide is the result of the individual motives of hostility directed at the self, and see cognitive theory that the cause of suicide is depression caused by the loss of hope and amplify the negatives. Mental disorders theory believes that the troubled tendency to self-stronger than the tendency of bad eggs destroyed. As you can see the theory (Durkheim) that the individual’s sense of social outcast that he and his community get him away leads him to commit suicide. Find out the Current search a set of conclusions and recommendations reached aimed at suicide prevention. Finally Find a set of proposals for future research progress.